265. Blood culture results pre- and post- antimicrobial administration in the Medicine Intensive Care Unit: a retrospective study in South Bronx. (31st December 2020) - Chiu, Chia-Yu; Sarwal, Amara; Feinstein, Addi
Abstract: Background: It is intuitive that obtaining blood cultures prior to administering antibiotics can increase the likelihood of a positive blood culture result. Surviving Sepsis Campaign Hour-1 bundle stipulates that obtaining a blood culture and administering antibiotics within 1 hour is a critical determinant of survival. However, the diagnostic sensitivity shortly after antibiotic administration remains unknown. In clinical practice, some health care providers delay antibiotic administration in order to first obtain a blood culture. Methods: Adult patients (> 18 years of age) admitted to the Medicine Intensive Care Unit in Lincoln Medical Center, located in South Bronx, New York City, from 09/2019 to 12/2019. Patients needed to have at least one blood culture obtained within 12 hours of admission and have received intravenous antibiotics during the admission to the Medicine Intensive Care Unit. Results: Of 327 patients screened, 196 met enrolment criteria and 253 sets of blood cultures underwent analysis. Blood cultures grew bacteria in 21.8% of pre-antimicrobial group whereas 26.9% in post-antimicrobial group ( p =0.37). 25.9% of patients received antibiotics within 1 hour before blood culture sampling, while 34.0% of patients received antibiotics >1 hour prior to obtaining blood culture. Blood culture results positive for coagulase-negative staphylococci were more prevalent in the pre-antimicrobial group. Table 1. Patient Characteristics Table 2. Number of blood cultures obtained and blood culture result Table 3. Initial antimicrobial agent and 30-day mortality Conclusion: In the sequence of blood culture and antibiotic administration, there is no 30-day survival difference in pre-antimicrobial group and post-antimicrobial group ( p =0.15), as long as both received antibiotics within 12 hours of coming to the hospital. Coagulase-negative staphylococci were higher in the pre-antimicrobial group which may indicate that the health care provider hastily obtained the blood culture in a non-sterile manner. Antibiotic administration should not be delayed because of pending blood culture collection. In addition, given that more than 70% of patients were ultimately found to have negative blood cultures, it would be useful to develop practical tools to identify low-risk patients that can be treated without obtaining blood culture, as the blood culture would not be likely to provide diagnostic information. Figure 1: Hours Before and After IV Antibiotic Started Figure 2: Distribution of Blood Culture Before and After IV Antibiotics Disclosures: All Authors : No reported disclosures